Daily report cards as a school‐based intervention for children with attention‐deficit/hyperactivity disorder. Issue 1 (February 2016) - Moore, Darren A.; Whittaker, Sarah; Ford, Tamsin J
Abstract : This paper describes daily report cards and the evidence relating to their use in schools for children with attention‐deficit/hyperactivity disorder (ADHD). This intervention typically involves teachers evaluating a student's behaviour at school against pre‐determined targets and parents subsequently providing reinforcement at home for positive reports. Research suggests that the daily report card has been effective in treating a range of ADHD symptoms and improving school outcomes, including academic achievement in some cases. The daily report card also encourages collaboration between teachers and parents, and evidence suggests that the intervention benefits from the inclusion of reinforcement at home. Daily report cards are easy to implement and research finds that teachers consider them an acceptable intervention for ADHD. This paper also considers challenges in using daily report cards, including barriers to their use over the long‐term and the risk of stigma for children with a report card. Ideas to address these issues are suggested.